2001
DOI: 10.1006/jnth.2000.2554
|View full text |Cite
|
Sign up to set email alerts
|

On a Problem of Schweiger Concerning Normal Numbers

Abstract: Let T and S be two number theoretical transformations on the n-dimensional unit cube B, and write TtS if there exist positive integers m and n such that T m =S n . F. Schweiger showed in [1969, J. Number Theory 1, 390 397] that TtS implies that every T-normal number x is S-normal. Furthermore, he conjectured that T t % S implies that not all T-normal x are S-normal. In this note two counterexamples to this conjecture are given. Academic Press

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…The following examples were shown by Kraaikamp and Nakada in [13]. Let β be a Perron number: an algebraic integer greater than one whose conjugates have modulus less than β. Handelman [5] showed that β has no other positive conjugates if and only if there exist an ℓ ∈ N and a nonnegative integer vector (a 1 , .…”
Section: Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The following examples were shown by Kraaikamp and Nakada in [13]. Let β be a Perron number: an algebraic integer greater than one whose conjugates have modulus less than β. Handelman [5] showed that β has no other positive conjugates if and only if there exist an ℓ ∈ N and a nonnegative integer vector (a 1 , .…”
Section: Examplesmentioning
confidence: 99%
“…Schweiger [22] and Vandehey [24] showed that if two number theoretic transformations T and S satisfy T m = S n for some positive integers n, m, then every T -normality is equivalent to S-normality. Kraaikamp and Nakada [13] gave counter examples that the other direction does not hold. They used the jump transformation to show the equivalence of normality: normality equivalence, in short.…”
Section: Introductionmentioning
confidence: 99%
“…Vandehey also showed the equivalence of normality with respect to the regular continued fraction expansion and with respect to the odd continued fraction expansion. C. Kraaikamp and H. Nakada [5] answered a conjecture of F. Schweiger [13] on normal numbers. The Q-Cantor series expansions, first studied by G. Cantor in [1], are a natural generalization of the b-ary expansions.…”
Section: Introductionmentioning
confidence: 96%
“…Theorem 1.4 (C. Kraaikamp and H. Nakada, 2001). There exist number-theoretic transformations S and T such that N(S) = N(T ) and such that there are no positive integers m and n with S m = T n .…”
Section: Introductionmentioning
confidence: 99%
“…So, for instance, it is known that N b = N b k for all b ≥ 2, k ∈ N [28], and it is known that N CF is the same as the set of normal numbers for certain continued fraction variants [23,37]. Some other examples of different digital systems with the same set of normal numbers can be found in [24,34]. On the other hand, few examples of systems with different sets of normal numbers are known.…”
Section: Introductionmentioning
confidence: 99%